EKOLOGI BUDAYA SEBAGAI WAWASAN POKOK DALAM PENGEMBANGAN MASYARAKAT UNTUK PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Nova Sudrajat Nur, Gian (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
This paper discusses local wisdom from local communities in Indonesiain environmental management of natural resources asimplementation of sustainable development. The purpose of this paper isprovide an overview of the forms of natural resource management andovercoming environmental problems based on local wisdom asinsight for community development activities. This research is descriptivequalitative analytical descriptive method using a theoretical approachcultural ecology through literature study. From the results of this study, it is known that the valuesculture in Indonesia tends to be ecocentric and biocentric, so it cansaid to be a deep ecology (ecology that is deep / concentrated). Apart from that, it was shown toocultural values ??regulate the management of natural resources wisely. This writingalso shows that local wisdom as cultural ecology is an insightimportant in community development activities because it is not just shapingindependence and creating prosperity. More than that, cultural ecology isembodiment of sustainable development.